The Engineering Pavilion – a learning space developing engineers for the global community - Tibbits, G.; Szymakowski, Jolanta; Maynard, Nicoleta; Tade, Moses; Jolly, L. (IEEE, 2014)
Of the many factors, formal and informal, that facilitate engineering students’ skills development and engineering identity, interactions with fellow students, teachers and industry are key. The Engineering Pavilion at Curtin facilitates these interactions in a building dedicated to students, providing a ‘home’ throughout their studies, a base for industry to engage with students, and stimulating concept understanding in a live (instrumented) building and learning space.To understand how students develop their learning, experience and behavior in this space, we need to understand the culture of the Pavilion. The theories of Pierre Bourdieu and the key concept of habitus, allow us to operationalize the concept of culture and understand the shifting mixtures of values and beliefs that underlie behavior. An ethnographic approach, studying a culture-shaping group at a single site, was employed.The Pavilion, recently opened, already supports student interactions. In moving from a habitus of student to graduate engineer, students’ perceptions and behavior are influenced by these interactions. The larger field of engineering education also changes through adoption or revaluing new forms of behavior through the curriculum. The Pavilion hosts the development of changing habitus and exemplifies how innovative learning spaces can influence the norms of long-established disciplines.